After Jews essays on political theology, Shoah and the end of man - Nowak, Piotr 1966- (Anthem Press, 2022)
Jews had lived with us for a thousand years. Then they were killed. Why? Had the Shoah always been brewing in these lands, or could it only happen under the conditions of late capitalism rather than in the atmosphere of primitive pogroms, the violent expulsion of Jews from their Anatevkas? An important point of reference for the author's reflections are the postulates of the representatives of the Frankfurt School - in particular of Max Horkheimer and Theodor W. Adorno's Dialectic of Enlightenment - who were the first to draw attention to the potentially criminal character of instrumental reason, disavowing at the same time the tradition of the siècle des Lumières, the approach which the author is inclined towards.